Mapping Glucose Uptake, Transport and Metabolism in the Bovine Lens Cortex - Zahraei, Ali; Guo, George; Varnava, Kyriakos G.; Demarais, Nicholas J.; Donaldson, Paul J.; Grey, Angus C. (Frontiers in Physiology, 2022)
Purpose: To spatially correlate the pattern of glucose uptake to glucose transporter distributions in cultured lenses and map glucose metabolism in different lens regions. Methods: Ex vivo bovine lenses were incubated in artificial aqueous humour containing normoglycaemic stable isotopically-labelled (SIL) glucose (5mM) for 5min-20 hours. Following incubations, lenses were frozen for subsequent matrix-assisted laser desorption/ionisation (MALDI) imaging mass spectrometry (IMS) analysis using high resolution mass spectrometry. Manually dissected, SIL-incubated lenses were subjected to gas chromatography-mass spectrometry (GC-MS) to verify the identity of metabolites detected by MALDI-IMS. Normal, unincubated lenses were manually dissected into epithelium flat mounts and fibre cell fractions and then subjected to either gel-based proteomic analysis (Gel-LC/MS) to detect facilitative glucose transporters (GLUTs) by liquid chromatography tandem mass spectrometry (LC-MS/MS). Indirect immunofluorescence and confocal microscopy of axial lens sections from unincubated fixed lenses labelled with primary antibodies specific for GLUT 1 or GLUT 3 were utilised for protein localisation. Results: SIL glucose uptake at 5 mins was concentrated in the equatorial region of the lens. At later timepoints, glucose gradually distributed throughout the epithelium and the cortical lens fibres, and eventually the deeper lens nucleus. SIL glucose metabolites found in glycolysis, the sorbitol pathway, the pentose phosphate pathway, and UDP-glucose formation were mapped to specific lens regions, with distinct regional signal changes up to 20 hours of incubation. Spatial proteomic analysis of the lens epithelium detected GLUT1 and GLUT3. GLUT3 was in higher abundance than GLUT1 throughout the epithelium, while GLUT1 was more abundant in lens fibre cells. Immunohistochemical mapping localised GLUT1 to epithelial and cortical fibre cell membranes. Conclusions: The major uptake site of glucose in the bovine lens has been mapped to the lens equator. SIL glucose is rapidly metabolised in epithelial and fibre cells to many metabolites, which are most abundant in the metabolically more active cortical fibre cells in comparison to central fibres, with low levels of metabolic activity observed in the nucleus.